Tinjauan Yuridis Pertanggungjawaban Pidana terhadap Ujaran Kebencian (Hate Speech) di Media Sosial - I Made Andy Sabda Permana; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Jurnal Konstruksi Hukum, 2022)
Unlimited freedom of expression causes hate speech crimes to occur more and more in society, especially on social media, especially related to this crime, there is still no special regulation as a regulation in minimizing cases like this. The purposes of this study are to examine the legal regulation of hate speech crimes through social media and criminal liability for hate speech through social media. This study uses normative law through a statutory and conceptual approach based on primary and secondary legal materials with document studies, then the results are presented in a descriptive analysis. The results of the study show that the basis for violating the law for those who make hate speech on social media is based on Law No. 11 of 2008 concerning ITE and Law No. 19 of 2016 on amendments to Law No. 11 of 2008. In accordance with legal regulations Therefore, the responsibility for hate speech crimes on social media is regulated in Article 45A paragraph (2) of Law Number 19 of 2016 which will be given a maximum imprisonment of 6 years and/or a maximum fine of 1,000,000,000.00 (One Billion Rupiah).